Gå så med glæde til dit arbejde - socialitet og sakramentalitet i Martin Luthers kaldslære - Krause Jørgensen, Eva (Slagmark - Tidsskrift for idéhistorie, 2018)
THEN GO TO YOUR WORK WITH JOY - SOCIALITY AND SACRAMENTAILITY IN MARTIN LUTHER'S TEACHING OF THE CALLING The article investigates Martin Luther’s teaching of the calling in a social perspective. In the tradition following the pioneering work of Max Weber, the Reformation has often been interpreted a steppingstone towards processes of disenchantment, secularization and rationalization. In recent years, a growing body of literature has argued that this tradition overlooks crucial elements of reformation spirituality such as sacramentality, sociality and the affirmation of ordinary life. With his conceptualization of work as a calling, Luther elevated and sanctified the everyday life and activities as a central component of the Christian life and the constitution of society. Here we might find the seed for the exceptionally high value ascribed to work in contemporary, Lutheran Nordic societies.